البيت الصامت وإفرازاته الإنحرافيةالأنثوية - قنيـفة, نــورة (Changement Social, 2018)
تعكس ظاهرة العلاقات العاطفية لدى المراهقات باعتبارها شكلا من أشكال السلوك الإنحرافي عن القيم و قواعد الضبط الأسرية والاجتماعية خللا في الوظائف الأسرية لاسيما في علاقتها المباشرة بأهم وظيفة أسرية هي الاتصال الأسري من جهة، وبخصوصية مرحلة المراهقة وإفرازاتها المزاجية وبالتالي السلوكية التي قد تصل حد الانحراف العلائقي (الجنسي بالخصوص) من جهة أخرى، الأمر الذي يجعلنا نؤكد على قوة الدور التواصلي بين المراهقة وأفراد الأسرة، خصوصا وأن الكثير من الطابوهات التي تمّ كسرها " افتراضيا" جعلتنا ننظر إليها علىأنها منتوج أفرزه البيت الصامت، البيت الذي يغيب فيه الاتصال الأسري أو بالأحرى يُغيّب نتيجة عمل الأم وتنازل أو استبعاد أو عدم التزام الأب بواجباته.. سنحاول من خلال هذه الورقة العلمية تقديم الظاهرة ميدانيا انطلاقا من عينة قصدية تعيش الظاهرة وتتفاعل معها مع محاولة رصد الخلل الوظيفي الأسري في بعده الاتصالي وإفرازاته النفس-اجتماعية. Romantic relationships among adolescents, as a form of deviant behavior that violates familial and social values and rules, is a phenomenon that reflects a defect in the family’s functions, especially in direct concern with two facts: first, communication as the most important function of family, and second, the specificity of adolescence and its temperamental, and thus behavioral, effects that may reach the degree of relational deviation (sexual in particular). In light of all this, we emphasize the power of communicative role between adolescent girl and family members, especially as a lot of taboos have been virtually broken leads us to consider it as a result for “the silent house”, the house that missed or forced to miss familial communication as a result of the mother work, and the exclusion or lack of the father's commitment to his duties.   We will try through this paper to provide a field research based on an intentional sample that live and interact with the phenomenon, and we will attempt to point the familial communication dysfunction and its psycho-social consequences.